Whom to Send to Doha? The Shortsighted Ones! - Mario Larch; Wolfgang Lechthaler (Kiel Institute for the World Economy (IfW), 2011)
Why are empirically observed tariffs so much lower than theoretically calculated Nash-equilibrium tariffs? We argue that this gap can be narrowed by using a dynamic model instead of a static model. This approach has two advantages. (i) It allows us to take account of the transitional process after a change in tariffs. (ii) It allows us to take account of the shortsightedness of policy makers. We show that Nash-equilibrium tariffs based on a dynamic trade model are lower than Nash-equilibrium tariffs based on a static model. We also show that shortsighted politicians tend to set lower tariffs than politicians with a long planning horizon.
Keywords: F11; F12; F13; 330; Bubbles; fiscal theory of the price level; collateral constraints; neutrality; transversality conditions; Zolltheorie; Nash-Gleichgewicht; Zollpolitik